Morphological and voltammetric characterization of different concentrations of spin coated Nafion-Ru(bpy)2+3 thin films - Tuason, Benjamin Simone B. (Animo Repository, 2015)
Different concentrations of Ru(bpy)2+3 were successfully deposited on ITO coated glass substrates employing a simple method using a spin coater. The surface morphology was determined by scanning electron microscopy (SEM). The transport mechanism and the diffusion coefficient of the redox mediators within the films were characterized using cyclic voltammetry (CV). The concentrations were varied by dissolving different amounts of the redox mediator in methanol and 5% Nafion. SEM micrographs showed that the roughness of the surface increased with concentration of redox mediator. CV showed successful incorporation of Ru(bpy)2+3. The order of the magnitude of the diffusion coefficients confirmed that the redox mediators were immobilized within the Nafion thin film. The resulting amount of redox mediator immobilized can be manipulated by simply varying the concentration of the casting solution.